Mengukur efektifitas poster anemia (media promosi kesehatan) untuk meningkatkan pengetahuan remaja tentang anemia - Siti Hajrianti; Theresia Shella Beredikta; Ida Tri Wahyuni (PT Nuansa Fajar Cemerlang, 2026)
Abstract Introduction : Anemia remains one of the significant public health problems among adolescents, particularly females, due to low knowledge and awareness regarding the importance of anemia prevention through proper diet and healthy behaviors. This study aims to measure the effectiveness of poster media as a health promotion tool in improving adolescents' knowledge about anemia. Methods : The approach employed is a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to review empirical evidence from scientific articles published between 2019 and 2025. Data were collected from various academic databases and analyzed using thematic narrative synthesis to identify patterns of findings, major categories, and research outcome trends. Result: The results indicate that poster media is effective in improving adolescents' knowledge and attitudes toward anemia prevention, particularly when combined with other educative approaches such as counseling, digital media, and family involvement. Poster media plays a significant role in simplifying health messages into visual forms that are easy to understand and cognitively engaging, thereby enhancing comprehension and behavioral prevention intentions. Discussion: Theoretically, this study reinforces the relevance of the Health Belief Model (HBM) in explaining the mechanisms of health behavior change through visual media. The implications of this research emphasize the importance of developing innovative, contextual, and behavioral theory-based health promotion media to support anemia prevention programs among adolescents.